Romanian Physical Education Teachers' Perception of Formative Feedback on their Professional Competencies - Drugău Sorin; Badau Dana; Nechita Florentina; Mijaica Raluca; Badau Adela; Iordan Andrei Daniel; Stanciulescu Robert; Dina George (Revista Romaneasca Pentru Educatie Multidimensionala, 2025)
The main purpose was to identify the formative perception of disciplines studied within the bachelor programs in Physical Education and Sports (PES) on the professional competence provided in the qualification sheets of the National Register of Qualifications in Higher Education (NRQHE) for the occupational qualification of Physical Education Teacher in primary and secondary education levels. Ranking the disciplines outlined in the Romanian Agency for Quality Assurance in Higher Education standards for the program in PES based on their impact on professional competencies (PC). 412 teachers: 284 junior teachers group (JTG) and 128 permanent teachers group (PTG). Online was filled out the Questionnaire (QAFISPES) for assessing the ranking of the disciplines provided in the Romanian Agency for Quality Assurance in Higher Education standards on PC in PES, structured on 3 subscales corresponding to the typology of the disciplines: fundamental, PE field, and specialized. For the Fundamental Disciplines subscale, the highest score per rank was Gymnastics had 5.75 points. For the subscale PE field disciplines, the greatest impact for PC in PES: the Theory and Practice of Athletics 11.25 points, the Theory and Practice of Gymnastics 11.08 points. For the subscale Specialized Disciplines, the most relevant contributions were made by the Methodology of Teaching Athletics in Schools 12.16 points, and the Methodology of Teaching Gymnastics in Schools 11.83 points. Establishing a hierarchy of disciplines based on their formative significance facilitates the optimal allocation of instructional hours within the bachelor's program's Physical Education and Sports (PES) curriculum.
Keywords: professional competence; junior teachers; permanent teaching; fundamental disciplines; PE field disciplines; specialized disciplines.